Benefits of using biosolid nutrients in Australian agriculture - a national perspective. - McLaughlin, M.; Bell, M.; Nash, D.; Pritchard, Deborah; Whatmuff, M.; Warne, M.; Heemsbergen, D.; Broos, K; Barry, G.; Penney, N. (Australian Water Association, 2008)
Increased nutrient levels in inland waterways have led to algal blooms and eutrophication in many agricultural regions. To ensure fertiliser inputs are managed more effectively, the source of contamination needs to be tracked and identified. Point sources could include inorganic fertilisers, livestock excreta, or more recently biosolids. The presence of faecal indicator microorganisms has been widely used to identify the presence of faeces, however, these methods cannot distinguish between human and animals samples. This study investigated PCR amplification as a molecular method to distinguish biosolids from livestock faeces of biosolids, cattle, sheep, poultry and kangaroo. This was achieved using published priming sequences and restriction site profiling of amplified DNA across the 16S rRNA gene of anaerobic gastrointestinal bacteria Bacteroides spp and Bifidobacteria spp. Preliminary investigation showed that of the three Bacteroides spp primer pairs investigated, two were useful for cow faecal material; though at lower annealing temperatures were also applicable to biosolids and sheep faecal material. The third primer pair was specific only for biosolids. All three primer pairs were unable to PCR-amplify Bacteroides spp sequences in faecal material of kangaroo. Of the three Bifidobacteria spp primer pairs, one was useful for sheep faecal material; though at lower annealing temperature was also applicable to biosolids and cow and kangaroo faecal material. The Bifidobacterium angulatum specific primer pair enabled the PCR detection of anaerobes only in biosolids and faecal material of kangaroo. The third, a Bifidobacterium catenulatum specific primer pair was suitable for faecal material of cow and at lower annealing temperatures was also applicable to the sample from sheep. Varying degrees of success were observed in faecal material from other animals. Generally, biosolids tested positive for Bacteroides and Bfidobacteria with all primers except for those specific for B. angulatum. For some primer sets, PCR amplification alone could not differentiate biosolids from other faecal samples. The serial dilution of water contaminated by a range of livestock excreta and biosolids is being examined further to enable the sensitivity of this method to be applied in the field.Soil acidification is an increasing problem throughout many agricultural regions in Australia typically on lighter-textured soils that have a low buffering capacity to changes in soil pH and/or that may be naturally acidic. Crops and pastures grown on acidic soils are subject to problems such as aluminium toxicity (particularly in the subsoil), nodulation failure in legumes and a reduced availability of some nutrients. Lime and dolomite are products that are commonly applied to neutralise soil acidity and improve plant productivity with application rates often determined by their neutralising value and particle size of the product, and the pH buffering capacity (lime requirement) of the soil. To investigate the effect of lime amended biosolids (LAB) as a product for neutralising soil acidity and for improving crop growth, four rates of LAB (0, 5, 10 and 15 t DS/ha) and four equivalent rates of lime product (0, 2.3, 4.6 and 6.7 t/ha) were applied to an acidic red/brown sandy loam in the central wheatbelt of Western Australia. In addition, one rate of dewatered biosolids cake (DBC) at 7 t DS/ha was included to enable comparison to be made to this product. The experiment was conducted over three years and sown to wheat (Triticum aestivum), canola (Brassica napus) and then wheat in 2005, 2006 and 2007, respectively. Plants were sampled at 8 weeks and at harvest to determine the effect of LAB, lime and DBC on crop growth, nutrient uptake and grain yield. Samples of surface soil (0-10 cm) were collected and analysed at harvest for pH and major nutrients. Soil pH increased significantly with increasing rates of LAB or lime at the end of the first year, with similar values recorded between equivalent values of lime product. There was no significant change in soil pH following the addition of the DBC treatment. No further changes in soil pH had occurred by the end of the second year. The growth of both wheat and canola in the first two years was affected to a greater extent by nutrients (typically nitrogen) in the LAB than by the reduction in soil acidity. Measurements on wheat yield in the third year of the experiment and changes in soil pH in the surface (0-10 cm) and subsoil (10-20 cm) will provide further information as to the long term effects of LAB in agriculture and allow recommendations to be made regarding best practise land application rates.